2009
DOI: 10.1258/acb.2008.008224
|View full text |Cite
|
Sign up to set email alerts
|

A patient with pseudo-Addison's disease and falsely elevated thyroxine due to interference in serum cortisol and free thyroxine immunoassays by two different mechanisms

Abstract: Interference in immunoassays is a widely recognized problem, which could potentially lead to unnecessary investigations and treatment. We describe a case where interference in a cortisol immunoassay led to a falsely low serum cortisol concentration and interference in the free thyroxine assay led to falsely elevated serum thyroxine concentrations, in the same patient. A 42-year-old woman with documented hypothyroidism underwent a synacthen test for suspected adrenal insufficiency. Previous thyroid function tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…There are also a limited number of cases reported to have interferences for more than one hormone. Saleem et al (20) described a case with falsely low cortisol and falsely elevated fT4 in the same patient; however, ACTH, FSH, LH, PRL, IGF-1, PTH, T, and dehydroepiandrosterone sulfate levels were all normal in this case. Fiad et al (21) demonstrated simultaneous artifactual elevations in T 4 , T 3 , and TSH assays.…”
Section: Discussionmentioning
confidence: 62%
“…There are also a limited number of cases reported to have interferences for more than one hormone. Saleem et al (20) described a case with falsely low cortisol and falsely elevated fT4 in the same patient; however, ACTH, FSH, LH, PRL, IGF-1, PTH, T, and dehydroepiandrosterone sulfate levels were all normal in this case. Fiad et al (21) demonstrated simultaneous artifactual elevations in T 4 , T 3 , and TSH assays.…”
Section: Discussionmentioning
confidence: 62%
“…Interference of endogenous substances in clinical samples result in the misinterpretation of a patient’s results leading to the wrong course of treatment [ 53 ]. It is reported that the serial dilution tests can verify the effect of interfering materials.…”
Section: Discussionmentioning
confidence: 99%
“…Since mice are used for monoclonal experiments, samples from patients exposed to mice (or treated with mouse monoclonal antibody therapies) can introduce heterophilic antibody reactions (88). Unusually low results for steroids can be found (89) and appropriate steps need to be taken to counteract the heterophilic antibodies (90, 91). To overcome concerns over safety and stability of reagents, alternative labels were introduced (chemiluminescent, fluorescent, as examples) (92), and from that time automation gradually took over (reviewed by Wheeler # 93).…”
Section: Immunoassays Of Steroidsmentioning
confidence: 99%